Exploring English Teachers’ Cognitions on the Implementation of Autonomous Learning - Fathi Husna, Dhia; Fauziati, Endang; Setyaningsih, Endang (International Journal of Educational Research & Social Sciences, 2024)
This study explores English as a Foreign Language (EFL) teachers' comprehension of autonomous learning and their strategies for fostering it. Utilizing qualitative research methods, including open-ended questionnaires and semi-structured interviews, data was gathered from teachers in Solo, Indonesia. The findings indicate that while teachers have a foundational understanding of autonomous learning, their practical application is still in the early stages. They recognize the significance of learner autonomy but often find it challenging to fully encourage students to learn independently. Although they express a desire to modify their teaching strategies to promote independence, they acknowledge the difficulties involved. The study underscores the necessity for further professional development to equip teachers with the knowledge and skills required to effectively promote autonomous learning in EFL classrooms. Future research should focus on strategies for supporting teachers in this area and examine the impact of autonomous learning on student outcomes.